Branched chain amino acids selectively promote cardiac growth at the end of the awake period. (August 2021) - Latimer, Mary N.; Sonkar, Ravi; Mia, Sobuj; Frayne, Isabelle Robillard; Carter, Karen J.; Johnson, Christopher A.; Rana, Samir; Xie, Min; Rowe, Glenn C.; Wende, Adam R.; Prabhu, Sumanth D.; Frank, Stuart J.; et al.
Abstract: Essentially all biological processes fluctuate over the course of the day, manifesting as time-of-day-dependent variations with regards to the way in which organ systems respond to normal behaviors. For example, basic, translational, and epidemiologic studies indicate that temporal partitioning of metabolic processes governs the fate of dietary nutrients, in a manner in which concentrating caloric intake towards the end of the day is detrimental to both cardiometabolic and cardiovascular parameters. Despite appreciation that branched chain amino acids impact risk for obesity, diabetes mellitus, and heart failure, it is currently unknown whether the time-of-day at which dietary BCAAs are consumed influence cardiometabolic/cardiovascular outcomes. Here, we report that feeding mice a BCAA-enriched meal at the end of the active period (i.e., last 4 h of the dark phase) rapidly increases cardiac protein synthesis and mass, as well as cardiomyocyte size; consumption of the same meal at the beginning of the active period (i.e., first 4 h of the dark phase) is without effect. This was associated with a greater BCAA-induced activation of mTOR signaling in the heart at the end of the active period; pharmacological inhibition of mTOR (through rapamycin) blocked BCAA-induced augmentation of cardiac mass and cardiomyocyte size. Moreover, genetic disruption of the cardiomyocyte circadian clock abolished time-of-day-dependent fluctuations in BCAA-responsiveness. Finally, we report that repetitive consumption of BCAA-enriched meals at the end of the active period accelerated adverse cardiac remodeling and contractile dysfunction in mice subjected to transverse aortic constriction. Thus, our data demonstrate that the timing of BCAA consumption has significant implications for cardiac health and disease. Graphical abstract: Unlabelled Image Highlights: The heart is primed for growth at the end of the active period. BCAAs stimulate rapid growth of the heart at the end of the active period. Eating BCAAs at the end of the active period exacerbates cardiac disease.